Pramūan kot rabīap kh̨ōbangkhap wādūai kānkhā læ kānlongthun Thai-ʻIndōčhīn - Phiphat R̄ưangngām; Thanyāthip Sīphanā; Māna Mālāphet (Singphim (Čhulālongk̨ōnmahāwitthayālai. Sathāban ʻĒchīasưksā), 1989)
Collection of rules and regulations relating to trade and investment between Thailand and Indochina.